2017
DOI: 10.1136/jim-2017-000445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sodium-Glucose Cotransporter 2 Inhibitors on Urinary Excretion of Intact and Total Angiotensinogen in Patients with Type 2 Diabetes

Abstract: We conducted a descriptive case study to examine the effects of sodium-glucose cotransporter 2 (SGLT2) inhibitors on urinary angiotensinogen excretion, which represents the function of the intrarenal renin–angiotensin system, in patients with type 2 diabetes. An SGLT2 inhibitor (canagliflozin 100 mg/day, ipragliflozin 25 mg/day, dapagliflozin 5 mg/day, luseogliflozin 2.5 mg/day or tofogliflozin 20 mg/day) was administered for 1 month (n=9). ELISA kits were used to measure both urinary intact and total angioten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 35 publications
0
38
0
1
Order By: Relevance
“…Other studies also showed no changes in albuminuria by SGLT2 inhibitors [27,30]. The issue is complicated in that the duration of treatment appears to influence the effects of treatment on albuminuria.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other studies also showed no changes in albuminuria by SGLT2 inhibitors [27,30]. The issue is complicated in that the duration of treatment appears to influence the effects of treatment on albuminuria.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, augmentation of AGT expression by high glucose and palmitic acid in cultured human PTC was blunted by Dapagliflozin [26]. In a small study, patients with T2DM, SGLT2 inhibitors exhibited a decreasing trend, but not significant, in urinary AGT excretion rates [27]. In contrast, the db/db mouse model of T2DM exhibited decreased renal AGT mRNA expression that was enhanced by treatment with an SGLT2 inhibitor [28] and increased urinary AGT levels in response to Empagliflozin treatment of the OLETF DM rat [29] has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results for biomarkers have suggested that the albuminuria-lowering effect of SGLT2is may be the result of decreased intraglomerular pressure or less tubular cell injury possibly related to decreased inflammation [117] and perhaps also linked to reduced activity of the intrarenal renin-angiotensin system [118]. SGLT2is also lower serum uric acid levels [119,120], an independent risk factor for diminished eGFRs in patients with T2DM [121,122].…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%
“…First, the Yoshimoto et al 1 study has been performed using different iSGLT2, even though they work in a similar way, they do not have the same potency blocking the SGLT2 receptors. In addition, the doses used are not comparable.…”
mentioning
confidence: 99%